1999
DOI: 10.1109/8.768806
|View full text |Cite
|
Sign up to set email alerts
|

Numerical optimization of a cylindrical reflector-in-radome antenna system

Abstract: Cataloged from PDF version of article.Accurate numerical optimization based on the rigorous\ud solution of the integral equation using the method of\ud analytical regularization is performed for the cylindrical reflector\ud antenna in a dielectric radome. It is shown that the multiple\ud scattering in this system is more significant for the optimum\ud radome design than any nonplane-wave effects or the curvature of\ud the radome. We claim that, although the common half-wavelength\ud design is a good approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…When the radome is considered the reflector surface and the radome may have the same axis i.e., the concentric one solved in [11] for both polarizations. The nonconcentric one which is widely used in practice especially for the small radome geometries was also analyzed by the combination of the MAR, Green's function and CSP methods in [12]. Then for the same problem the solution was tried to be improved by the usage of the available FFT algorithm in the computation of the Green's function in [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…When the radome is considered the reflector surface and the radome may have the same axis i.e., the concentric one solved in [11] for both polarizations. The nonconcentric one which is widely used in practice especially for the small radome geometries was also analyzed by the combination of the MAR, Green's function and CSP methods in [12]. Then for the same problem the solution was tried to be improved by the usage of the available FFT algorithm in the computation of the Green's function in [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a variety of different approaches have been employed to investigate the modification of the radiation pattern of an antenna covered by a radome. These approaches can be divided into three categories: 1) high-frequency (HF) methods such as the ray-tracing technique [1][2][3]; the plane wave spectrum-surface integral technique [4], the physical optics method (PO) and dielectric physical optics (DPO) technique [5]; 2) low-frequency (LF) methods such as the method of moments (MoM) [6,7]; the finite element method (FEM) [8], and the method of regularization (MOR) [9]; and 3) analytical methods such as the dyadic Greens function method and iterative interaction procedure [10,11] which provide more physical insight but are applicable to radomes of special shapes. An important assumption of high frequency methods is that the structures have smooth surfaces and electrically large radii of curvature.…”
Section: Introductionmentioning
confidence: 99%
“…This configuration is used more frequently in applications to model smaller radomes. In [16], the cylindrical reflector-in-radome antenna system was solved again by combining MoR, Green's function technique and CSP method. Furthermore in this study, it is observed that the radiation characteristics of the free space reflector antenna system can be improved by the proper selection of the nonconcentric radome parameters i.e the radome thickness, its radius, the reflector location inside the radome and the position of the feed.…”
Section: Introductionmentioning
confidence: 99%
“…It is also assumed that the radome and reflector surfaces have circular profiles. In the previous study in [16], a similar radome-enclosed reflector antenna system was analyzed for H-polarization case for the moderately-sized geometries. But here it is studied especially for the E-polarization case and even for the larger dimensional geometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation